Духовно-нравственное воспитание младших школьников через использование свободного программного обеспечения в учебно-воспитательном процессе начальной школы - Markushevich M. V., Pogosova O. V. (Psychology and Pedagogics in the 21st century: theory, practice and perspectives, 2017)
The article is devoted to a software choice problem in teaching and educational process of elementary school. Authors place emphasis on the spiritual and moral side of this problem.
Keywords: учебно-воспитательный процесс; программное обеспечение; начальная школа; elementary school; freeware; free software; teaching and educational process